Paraguay : 2017 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Paraguay has grown robustly despite a more challenging external environment. The economy gained momentum toward the end of 2016 and expanded by 6.5 percent (year-over-year) during the first quarter of 2017. Real GDP growth is projected to reach 4.2 percent in 2017, reflecting a more moderate pace of activity in the second half of the year. Investment will likely be a crucial driver of growth, as major infrastructure projects are undertaken. Over the medium term, real GDP growth is expected to remain near potential of just below 4 percent. Risks around the outlook are to the downside, especially from heightened political uncertainty in Brazil.